Single crystal surface investigations using RHEED. - Bulicz, John. (University of Ottawa (Canada), 1992)
A RHEED system was assembled and incorporated in the existing ultra-high-vacuum chamber. A system for the production and transport of low energy ions to the ultra-high-vacuum environment was maintained. Samples cut from wafers of Si(100) were investigated using electron diffraction as well as low energy ion scattering techniques. The surface composition, symmetry and orientation of these specimens could be determined. Attempts to adsorb hydrogen onto the Si(100) surface indicated that the procedure in use needs to be modified. An initial RHEED study of the Si(110) surface revealed a complex arrangement of atoms which does not correspond to the "16 x 2" structure reported for the clean surface.
Keywords: Physics, Condensed Matter.